Formation of the enterprise's strategy in the current innovative transformations - Onyshchenko, Oksana (Management and Entrepreneurship: Trends of Development, 2017)
Purpose. The paper purpose is to study the issues of strategic development of domestic enterprises in the conditions of modern innovative transformations.Design/methodology/approach. The basic principles of the research are historical, systematic and comparative methods, institutional and structural-functional approaches have been used.Findings. The subject of the study is the theoretical, methodological aspects and practical applications of the formation and implementation of enterprise strategies. The relevance of the research is determined by the need to increase the level of innovation in the production potential of domestic entrepreneurship, taking into account the determining role of innovations in the development of the country's economy. Current world economic situation is characterized by the increasing role of scientific and technological progress in ensuring the competitiveness of national economies. That is why the development of innovative scientific and technical spheres is of significant strategic importance. The innovation management theoretical issues and practical research are especially important for SMEs as the main subjects of microeconomics, which have to formulate appropriate strategies, introducing the innovative products and technologies for ensuring sustainable development in the conditions of modern innovative transformations. As a conclusion the need to enhance innovation activity of domestic business using relevant development strategies is substantiated.Research limitations/implications. The paper clearly provides direction for strategic development of enterprises taking into account the specific features of the development of innovative activity in Ukraine.Originality/value. Such knowledge will help to increase the competitiveness of the Ukrainian economy and accelerate the process of integrating the country into the world economy. Further research on the development of domestic enterprises in the context of modern innovation transformations is significantly actualized in the process of Ukraine's integration into the world economy, since an exceptionally high level of innovative activity of enterprises is a prerequisite for achieving a sufficient level of efficiency of the domestic market and ensuring the competitiveness of the national producer products